The function of the imaginary. Garroni, Mannoni and the voluntary illusion - Restuccia, Francesco (Aesthetica Preprint, 2022)
In his 1969 “Je sais bien, mais quand-même” Octave Mannoni rethinks the concept of Verleugnung, analyzing how a belief can subsist despite denial by reality, yet becoming elusive and insubstantial. Mannoni’s text was published in Italy by Emilio Garroni, who wrote an introductory essay, in addition to mentioning him a couple of times in his works. Garroni observes that this way of thinking illusion – as an intermediate stage between deception and disillusionment – may prove useful in understanding the function of the imaginary in culture. Mannoni’s theory might have helped Garroni realizing, as early as 1972, that all human cultural activity, even philosophy and science, necessarily relates with lower levels of consciousness, which are both denied and confirmed. The paper traces the development of Garroni’s reflections on the relationship between belief, illusion and awareness, from the introduction to Mannoni’s essay until his writings on magical thinking in the late 1990s and early 2000s. This implicit, reconstructed dialogue between Mannoni and Garroni may prove useful not only in understanding ancient and contemporary magical thinking, but also in rethinking the concept of fiction in light of the new immersive and hyperrealist image-making techniques.